ZASADA INDYWIDUALIZACJI KARY NA GRUNCIE KODEKSU KARNEGO Z 1997 R. - Szczepaniec, Maria (Zeszyty Prawnicze, 2016)
THE PRINCIPLE OF INDIVIDUALISED PUNISHMENT ON THE GROUNDS OF THE POLISH CRIMINAL CODE OF 1997 Summary The article presents an analysis of the principle of individualised punishment incorporated in the Polish Criminal Code. The main difficulties involved are the circumstances affecting the severity of the sentence imposed. The article gives a classification of these circumstances and a short description of some of them .The diversified effect of particular circumstances may be connected with a specific directive prioritised in the given individual sentence.